2001
DOI: 10.1051/vetres:2001143
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and necrosis of blood and milk polymorphonuclear leukocytes in early and midlactating healthy cows

Abstract: -Increased milk somatic cell counts (SCC) are used as an indicator for bovine mastitis. During mastitis, polymorphonuclear leukocytes (PMN) become the predominant cell type. Shortly after parturition, the severity of mastitis is increased and several PMN functions are downregulated. Apoptotic and necrotic processes of PMN could influence SCC and PMN functions. In this study, the percentages of apoptotic and necrotic PMN in blood and milk from early and midlactating healthy cows were compared. Apoptosis and nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 12 publications
5
31
0
4
Order By: Relevance
“…These neutrophils were found in both the early and late stages of apoptosis, which was verified by the detection of translocated phosphatidylserine in FCM and karyopyknotic nuclei in LM. The presence of apoptotic neutrophils already in the acute-phase response can be explained as follows: (i) neutrophils have a short life-span of 1-2 days and they are predisposed for spontaneous apoptosis [17], (ii) neutrophils are recruited from the bloodstream in various age-phases [8], (iii) apoptosis in neutrophils is induced by migration into the lumen of the mammary gland [28], (iv) another, certainly non-omissible effect is the effect Figure 6. Transmission electron microscopy of macrophage with phagocytosed apoptotic neutrophils (asterisks) and bacteria (arrow).…”
Section: Discussionmentioning
confidence: 99%
“…These neutrophils were found in both the early and late stages of apoptosis, which was verified by the detection of translocated phosphatidylserine in FCM and karyopyknotic nuclei in LM. The presence of apoptotic neutrophils already in the acute-phase response can be explained as follows: (i) neutrophils have a short life-span of 1-2 days and they are predisposed for spontaneous apoptosis [17], (ii) neutrophils are recruited from the bloodstream in various age-phases [8], (iii) apoptosis in neutrophils is induced by migration into the lumen of the mammary gland [28], (iv) another, certainly non-omissible effect is the effect Figure 6. Transmission electron microscopy of macrophage with phagocytosed apoptotic neutrophils (asterisks) and bacteria (arrow).…”
Section: Discussionmentioning
confidence: 99%
“…Midlactating cows were preferred to early lactating cows to avoid possible interference caused by isolation of PMN from animals with high plasma NEFA consequent to intense lipomobilization. Furthermore, midlactation is a period during which most of the concerned cell functions are optimal in comparison with their status at early lactation (Van Oostveldt et al, 2001). Cows were selected from the dairy herd at Gent University (Biocentrum Agri-Vet, Melle, Belgium) and at the time of the study, average milk yield was approximately 23 L/d.…”
Section: Animals and Blood Sample Collectionmentioning
confidence: 99%
“…Recently, Mehrzad et al (2004Mehrzad et al ( , 2005 also demonstrated that chemiluminescence and viability of resident milk PMN (static innate immunity) play a crucial role in the severity of subsequently induced Escherichia coli mastitis. Finally, Van Oostveldt et al (2001) reported that apoptosis of circulatory and milk PMN was higher in early lactating than in midlactating cows; those researchers suggested that apoptotic and necrotic processes might explain the downregulation of PMN functions shortly after calving.…”
Section: Introductionmentioning
confidence: 99%
“…In cows, PMN apoptosis is influenced by stage of lactation. In one study, blood was obtained from early lactating (13 6 days after parturition) and mid-lactating (170 26 days after parturition) cows and subsequently incubated for four hours to induce apoptosis [175]. PMN isolated from the blood of early lactating cows demonstrated a higher rate of apoptosis than PMN derived from mid-lactating cows.…”
Section: Regulation Of Pmn Life Spanmentioning
confidence: 99%